تحليل أثر المتغيرات الوسيطية في نموذج المعادلات البنائية باستخدام طريقة"bootstrapping" دراسة حالة أثر الرضى والثقة على ولاء زبائن شركة موبيليس لاتصالات الهاتف النقال بالجزائر - نعيجات, عبد الحميد; بداوي, محمد (جامعة الوادي - University of Eloued, 2022)
ناقشت هذه الدراسة طريقة فعالة في ميدان الاحصاء لتحليل الوساطة وتوفير بدائل أكثر دقة، ولقد عالجت هذه الورقة تأثير رضى ودرجة ثقة الزبائن على ولاء زبائن شركة موبيليس بالأغواط. وأبرزت هذه الدراسة أهمية التأثير غير المباشر فيما يتعلق بحجم الوساطة. وأكد الاستطلاع على وجود تأثير للثقة كوسيط، حيث وجدت وساطة جزئية بين رضى الزبائن وولاء زبائن شركة موبيليس بالأغواط. This studyDiscussed the use Bootstrapp in the mediationanalysiscontext ; new procedures have been adopted by providing more accurate alternatives, thisresearch has analyzed the impact of Customer satisfaction and trust on Mobilis’ customersloyalty (CL) , and highlighted the indirect influence of mediation size. The survey conducted by the researchers has confirmed the impact of customers Trust (CT) as a mediator, a partial mediation between Customer satisfaction and costumers’ loyalty has been founded.
Analysis the impact of the mediation variables in the structural equations modelusing the "Bootstrapping" method A case study of satisfaction and trust on customers loyalty in Mobilis company, Algeria
مقال
Keywords: وساطة ; رضى الزبائن ; ثقة الزيائن ; ولاء الزبائن